Вплив музики з різними фрактальними розмірностями на людину - Бігун, М. Д.; Юсова, П. Д. (ХНУРЕ, 2025)
In the publication, the impact of the fractal dimension of music on human perception is explored. It examines genres such as classical (D=1.1), jazz (D≈1.1), rock (D=1.5), and pop music (D=1.8). It was found that lower fractal dimensions contribute to relaxation, while higher dimensions lead to emotional excitation. Classical music and jazz enhance concentration, rock stimulates dopamine, and pop music affects mood depending on the content. The study of this topic opens up prospects for further investigation into the connection between the fractal dimension of music and its effects.
Keywords: вплив музики; fractal dimension of music